Features of Russia migration policy in the 1990 - Morozov Sergej (Traektoriâ Nauki, 2016)
The article considers the main directions of Russia migration policy after the Soviet Union collapse. The analysis of the dynamics of the accommodation of refugees and internally displaced people on the territory of Russia is made.